1998
DOI: 10.1083/jcb.142.4.975
|View full text |Cite
|
Sign up to set email alerts
|

Transient Mitochondrial Depolarizations Reflect Focal Sarcoplasmic Reticular Calcium Release in Single Rat Cardiomyocytes

Abstract: Digital imaging of mitochondrial potential in single rat cardiomyocytes revealed transient depolarizations of mitochondria discretely localized within the cell, a phenomenon that we shall call “flicker.” These events were usually highly localized and could be restricted to single mitochondria, but they could also be more widely distributed within the cell. Contractile waves, either spontaneous or in response to depolarization with 50 mM K+, were associated with propagating waves of mitochondrial depolarization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
210
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(225 citation statements)
references
References 41 publications
13
210
2
Order By: Relevance
“…Several studies indicate that by buffering [Ca 2+ ] c , rapid mitochondrial Ca 2+ uptake directly affects EC coupling [61,100,117,119,124,147,148,171]. When blocking mitochondrial Ca 2+ uptake, an increase of cytosolic Ca 2+ transients was observed ( Fig.…”
Section: Implications Of Rapid Mitochondrial Ca 2+ Uptake For Ec Coupmentioning
confidence: 95%
See 2 more Smart Citations
“…Several studies indicate that by buffering [Ca 2+ ] c , rapid mitochondrial Ca 2+ uptake directly affects EC coupling [61,100,117,119,124,147,148,171]. When blocking mitochondrial Ca 2+ uptake, an increase of cytosolic Ca 2+ transients was observed ( Fig.…”
Section: Implications Of Rapid Mitochondrial Ca 2+ Uptake For Ec Coupmentioning
confidence: 95%
“…6D; [12,117]). Accordingly, localized Ca 2+ sparks induced transient focal depolarizations of Δψ m by ∼10-15 mV [61]. The propagation of caffeine-induced Ca 2+ sparks was suppressed by mitochondria, since inhibition of the mCU (with Ru360) resulted in regenerative Ca 2+ waves across the whole cell [171].…”
Section: Implications Of Rapid Mitochondrial Ca 2+ Uptake For Ec Coupmentioning
confidence: 98%
See 1 more Smart Citation
“…The researchers proposed that these partial, transient depolarizations may reflect the mitochondria alternating between active and inactive oxidative phosphorylation [63]. Other studies have also shown mitochondrial membrane potential changes in isolated mitochondria [64,65], and in mitochondria within different cell types, such as cardiomyocytes [66], vascular endothelium [65], and pancreatic B-cells [67]. Buckman and Reynolds found that oligomycin, which inhibits ATP-synthase, decreased the number of fluctuations, suggesting that the fluctuations are related to oxidative phosphorylation [63].…”
Section: Influence Of Respiration On the Cellular Levelmentioning
confidence: 99%
“…This omission generally has been justified by findings that the role of mitochondria as a calcium sink or source in beat-to-beat regulation of the cytosolic calcium concentration is rather small (Bassani et al 1992). However, recent results from various groups suggest that mitochondrial calcium uptake and release can have a significant effect on cellular calcium homeostasis (Duchen et al 1998, Trollinger et al 2000, see Dedkova and Blatter (2008) for a review. Thus, it appears that the addition of a mitochondrial calcium compartment should be addressed in future modelling studies.…”
Section: Models Of Calcium Signalling In Cardiac Cellsmentioning
confidence: 99%